FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR PADA BURSA EFEK INDONESIA (BEI) (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia (BEI) Tahun 2013-2015) - Amy Sintia Dewi, 13.05.62.0029; Jaeni, Jaeni (Students Journal of Accounting and Banking, 2017)
This study aims to examine and analyze the effect of profitability, solvency, the auditors opinion, the size of the company, size of public accounting firms and age of the firm to audit delay on manufacturing companies listed in Indonesia Stock Exchange (BE). The population of this research is manufacturing companies listed in Indonesia Stock Exchange (BEI) during the years 2013 to 2015 that reported complete financial statements and published in Indonesian Capital Market Directory (ICMD) and IDX website. Samples are included in the criteria of this study were 99 companies using purposive sampling method. Methods of data analysis in this study using multiple linear regression analysis using SPSS 19. The results showed that the variables of solvency, the auditors opinion, the size of the public accounting firms are not significant positive effect on audit delay, variable sized companies significant negative effect on audit delay, and variable age of company profitability and significant negative effect on audit delay.Keywords: Audit Delay, Profitability, Solvency, The Auditors Opinion, The size of The Company, The Size of The Public Accounting Firm (KAP) and The Age of The Company